Application of Just in Time Method in Sales Management of Gas Safety Equipment (Regulators and Hoses) at PT. Sarana Anugerah Nusantara - Christian Adi Darma; Asnawati Asnawati; Sapri Sapri (Perkumpulan Dosen Muda (PDM) Bengkulu, 2021)
PT. Sarana Anugerah Nusantara is the largest LPG product company in Indonesia, which currently has 20 branch offices. PT. Sarana Anugerah Nusantara is engaged in consulting services, technique and marketing of LPG products. PT. Sarana Anugerah Nusantara has superior LPG products in the form of a Solid regulator which is equipped with a gas safety hose that automatically closes in the event of a leak so it is safe to use. Solid regulator also has a nanometer matic so it is more accurate to determine the contents of gases made of a mixture of copper and aluminum. So far, the sales system for gas safety equipment (regulators and hoses) is still using the manual method through bookkeeping (data attached). Constraints that are often faced are the difficulty of managing inventory at PT. Sarana Anugerah Nusantara and difficulties in collecting data on consumers who use these goods. Sales management application for Gas Safety Equipment (Regulator and Hose) at PT. Sarana Anugerah Nusantara was created using the Visual Basic .Net programming language. This application has applied the Just In Time Method which can help sales management of gas safety devices (regulators and hoses) based on inventory data and sales data. With the application can make it easier for PT. Sarana Anugerah in the management of the sale of goods and can manage the data of incoming and outgoing goods systematically through the application. Based on the black box testing that has been done, the results show that the functionality of the sales management application for Gas Safety Equipment at PT. Sarana Anugerah Nusantara is running as expected.